2013
DOI: 10.1083/jcb.201208008
|View full text |Cite
|
Sign up to set email alerts
|

Condensin II initiates sister chromatid resolution during S phase

Abstract: Condensin II initiates structural reorganization of duplicated chromosomes during S phase to prepare for their proper condensation and segregation in mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 42 publications
4
77
0
Order By: Relevance
“…A recent study has shown that condensin II initiates its action during S phase and counteracts cohesin-mediated cohesion (Fig. 3B) (Ono et al 2013). A combination of two functional assays, premature chromosome condensation (PCC) and fluorescence in situ hybridization (FISH), revealed that condensin II associates with duplicated regions of chromosomes and promotes their "resolution" during S phase.…”
Section: Condensin II Initiates Its Action Long Before Entry Into Mitmentioning
confidence: 90%
“…A recent study has shown that condensin II initiates its action during S phase and counteracts cohesin-mediated cohesion (Fig. 3B) (Ono et al 2013). A combination of two functional assays, premature chromosome condensation (PCC) and fluorescence in situ hybridization (FISH), revealed that condensin II associates with duplicated regions of chromosomes and promotes their "resolution" during S phase.…”
Section: Condensin II Initiates Its Action Long Before Entry Into Mitmentioning
confidence: 90%
“…It was also speculated that promotion of the ssDNA annealing by Smc2/Smc4 could be required to remove "leftover" products of interphase processes, such as DNA-RNA hybrids, from mitotic chromosomes to facilitate their faithful segregation (38). This scenario might be related to the initiation of sister chromatid resolution during the S phase by condensin II (39).…”
Section: Volume 290 • Number 49 • Decembet 4 2015mentioning
confidence: 99%
“…In addition to its role in mitotic chromosome condensation, chromosome shape, and controlling recombination, Condensin II has also been implicated in DNA replication and damage repair ( 12 ). In particular, Condensin II functions in the resolution of sister chromatids immediately following replication in S-phase ( 13 ). Despite these roles for Condensin II, we know little about how it is recruited to specifi c genomic locations, such as repetitive sequences, to carry out these functions.…”
Section: Introductionmentioning
confidence: 99%